THE EFFECT OF VISUAL COMMUNICATION ON “CANTIK FEST” IN TOKOPEDIA TOWARDS BUYING INTEREST OF FEMALE CONSUMER IN JAKARTA - Marilyn; Sitinjak, Tony (Jurnal Komunikasi dan Bisnis, 2022)
Humans are facilitated by technological advances where consumers can do online shopping anywhere and anytime through the E-Commerce platform. Tokopedia has one of the biggest campaigns, namely “Cantik Fest” and creates a visual communication, one of that is through banners in Tokopedia application which is related to how prospective buyers will be interested in shopping online. The purpose of this research is to find out and get an idea about the effect of visual communication "Cantik Fest" which is expressed in the form of a banner on the homepage of the Tokopedia application towards buying interest of female consumers in Jakarta. This study uses a quantitative method with a sampling technique that is purposive sampling. The data collection technique was through distributing questionnaires to female residents in the Jakarta area who had the Tokopedia online shopping application as many as 99 respondents. The results obtained from the data analysis test in this study indicate that the visual communication affects the variable Y (buying interest), declared that there is an influence of visual communication "Cantik Fest" on Tokopedia towards buying interest of female consumers in Jakarta. This is indicated by the results of the study of visual communication variables affecting the buying interest variable by 88.9%. The conclusion of this study by testing 99 respondents to female residents in Jakarta who have the Tokopedia application, it is stated that there is an effect of "Cantik Fest" visual communication conducted by PT. Tokopedia towards buying interest of female consumers in Jakarta.